A novel method for analysis and prediction of methanol mass transfer in direct methanol fuel cell. (15th December 2017) - Ji, Feng; Yang, Linlin; Sun, Hai; Wang, Suli; Li, Huanqiao; Jiang, Luhua; Sun, Gongquan
Highlights: A novel method for measuring methanol mass transfer coefficient is developed. Catalyst layer methanol concentration obtained from methanol crossover flux. A mass transfer correlation is deduced using dimensional analysis. MEA optimization & fuel utilization evaluation based on the correlation is performed. A maximum power density of 178 mW/cm 2 operated with atomistic air is achieved. Abstract: Two-phase gas/liquid flows coupled with electrochemical reactions in the anode of direct methanol fuel cell (DMFC) are quite complicated transport phenomena. The methanol transport is a key factor influencing the performance as well as fuel utilization efficiency. In this paper, a dimensionless correlation of methanol mass transfer in DMFC anode is proposed. Firstly, a method for detecting methanol concentration in catalyst layer was developed, which is the key parameter to obtain the mass transfer coefficient. Then, the influences of the various factors on the mass transfer coefficient, including physical properties of fluid, structures of the electrode, cell configuration and cell operation conditions, were investigated. And a correlation between four dimensionless groups, i.e., Sh, Re, Sc and Π (ratio of consumption and feeding rate of methanol), was deduced using the dimensional analysis. Finally, MEA optimization and fuel utilization efficiency evaluation based on the above analysis is performed. A maximum power density of 178 mW cm −2 at 80 °C and atomistic air is achieved, 40% higher than that of commercial one made by Johnson Matthery.